2022
DOI: 10.1371/journal.pone.0268596
|View full text |Cite
|
Sign up to set email alerts
|

Unconstrained coevolution of bacterial size and the latent period of plastic phage

Abstract: Viruses play critical roles in the dynamics of microbial communities. Lytic viruses, for example, kill significant fractions of autotrophic and heterotrophic microbes daily. The dynamic interplay between viruses and microbes results from an overlap of physiological, ecological, and evolutionary responses: environmental changes trigger host physiological changes, affecting the ecological interactions of host and virus and, ultimately, the evolutionary pressures influencing the two populations. Recent theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…2). This plasticity may suggest adaptive strategy in presence of stressors, as observed in various biological systems such as intestinal microbiota, coral reefs, marine life, and wildlife populations (Candela et al, 2012;Reusch, 2014;Torda et al, 2017;Leray et al, 2021;Bonachela et al, 2022;Risely et al, 2023;) Next, we identified niche differentiating parallel SNVs retained throughout the growing season. Putative adaptive SNVs differentiating between resistant and susceptible cultivar under ambient environment were of interest.…”
Section: Discussionmentioning
confidence: 89%
“…2). This plasticity may suggest adaptive strategy in presence of stressors, as observed in various biological systems such as intestinal microbiota, coral reefs, marine life, and wildlife populations (Candela et al, 2012;Reusch, 2014;Torda et al, 2017;Leray et al, 2021;Bonachela et al, 2022;Risely et al, 2023;) Next, we identified niche differentiating parallel SNVs retained throughout the growing season. Putative adaptive SNVs differentiating between resistant and susceptible cultivar under ambient environment were of interest.…”
Section: Discussionmentioning
confidence: 89%